Pharmacognostic studies of Trifolium fragiferum L. flora of Southern Ukraine - O. V. Grechana; A. H. Serbin; O. O. Salii; A. M. Rudnyk; I. M. Shevchenko; L. A. Fukleva (Zaporozhye State Medical University, 2022)
The work is devoted to the study of herbs of the representative genus Clover Trifolium fragiferum L. from the south Ukrainian flora. The aim of this research is to investigate the representative of Southern Ukraine flora Trifolium fragiferum L. which has a sufficient raw material base and use in folk medicine. Materials and methods. Samples were grown in the suburbs of Zaporizhzhia and harvested during full flowering (May - June). Microscopic analysis was performed with temporary preparations of leaves and stems. Plant extracts were analyzed chromatographically using an Agilent Technologies 6890 gas chromatograph with mass spectrometric detection. Results. The leaf is covered with parenchymal cells with slightly thickened membranes with anocytic stomata. The main parenchyma is composed of rounded toxoid cells. Stem rounded, covered with elongated parenchymal cells with thin membranes with almost no stomata and pubescence. Central axial cylinder is of beam type. Beams are open collateral, large. Above the phloem of the bundles is a multilayered sclerenchyma. The core is partially filled, hollow in the center. 63 compounds were found in the native extract, of which 37 were identified: coumarins, fatty acids, diterpene alcohols, oxygenated hydrocarbons of terpenoid nature, higher hydrocarbons, representatives of phytosterols, and phytosterols. After acid hydrolysis with sulfuric acid, 58 compounds were found, of which 49 were identified: coumarins, alcohols and phenols, aldehydes and ketones, compounds of diterpene nature. Conclusions. Pharmacognostic analysis of the genus Clover Trifolium fragiferum L. revealed diagnostic microscopic signs of leaves and stems. The components of the native extract are compared, and after its acid hydrolysis. Certain regularities in the distribution of classes of substances that characterized certain types of extracts were revealed: monoterpenoids, aromatic, heterocyclic compounds characterized the hydrolyzed product. Sesquiterpenes and steroid compounds are found only in the native extract of strawberry clover herb. Alcohols, aldehydes, and ketones were the majority in the hydrolyzed extract, and hydrocarbons were observed more in the native. Only 5 components were identified in both extracts: nonacosan, 2-phenoxyethanol, loliolide, dihydroactinidiolide and coumarin with significant differences in amounts.